Characterization of Wnt and Notch-Responsive Lgr5+ Hair Cell Progenitors in the Striolar Region of the Neonatal Mouse Utricle - You, Dan; Guo, Luo; Li, Wenyan; Sun, Shan; Chen, Yan; Chai, Renjie; Li, Huawei (Frontiers in Molecular Neuroscience, 2018)
Dysfunctions in hearing and balance are largely connected with hair cell (HC) loss. Although regeneration of HCs in the adult cochlea does not occur, there is still limited capacity for HC regeneration in the mammalian utricle from a distinct population of supporting cells (SCs). In response to HC damage, these Lgr5+ SCs, especially those in the striolar region, can regenerate HCs. In this study, we isolated Lgr5+ SCs and Plp1+ SCs (which originate from the striolar and extrastriolar regions, respectively) from transgenic mice by flow cytometry so as to compare the properties of these two subsets of SCs. We found that the Lgr5+ progenitors had greater proliferation and HC regeneration ability than the Plp1+ SCs and that the Lgr5+ progenitors responded more strongly to Wnt and Notch signaling than Plp1+ SCs. We then compared the gene expression profiles of the two populations by RNA-Seq and identified several genes that were significantly differentially expressed between the two populations, including genes involved in the cell cycle, transcription, and cell signaling pathways. Targeting these genes and pathways might be a potential way to activate HC regeneration.